Postpartum depression and maternal-infant bonding: the mediating role of mentalizing and parenting self-efficacy - Weijing Qi; Ziqi Wei; Huicong Lv; Jinping Zhao; Yuanyuan Hu; Yitong Wang; Qing Guo; Jie Hu (BMC Pregnancy and Childbirth)
Abstract Background The accumulated evidence suggested that postpartum depression was mainly associated with maternal-infant bonding. However, this link needed to be further explained by potential mediating factors. This study aimed to investigate the impact of postpartum depression on maternal-infant bonding, examining the mediating roles of mentalizing and parenting self-efficacy. Methods A sample of 390 postpartum women was recruited from a maternity hospital around four weeks postpartum. A multiple mediating analysis was conducted to investigate how mentalizing and parenting self-efficacy affected the relationship between postpartum depression and maternal-infant bonding. Results The mediation analyses indicated that postpartum depression had a direct negative impact on maternal-infant bonding among postpartum women. It could also exert an indirect effect via three pathways: the independent mediation of parenting self-efficacy, the serial mediation of hypermentalizing and parenting self-efficacy, and the serial mediation of hypomentalizing and parenting self-efficacy. Limitations Women were sampled from a single maternity hospital, and self-report measures were utilized. The cross-sectional design also limited conclusions about causation and directionality. Conclusions The findings suggest that postpartum depression may negatively affect maternal-infant bonding. Moreover, the significant roles of a mother’s mentalizing and parenting self-efficacy in the relationship between postpartum depression and maternal-infant bonding should not be overlooked. These results could offer insights into supporting women with postpartum depressive symptoms to establish positive mother-infant relationships. Clinical trial number No. 20230128.